Revitalizing Justice in Fiqh: Revisiting Non-Retroactive Principles to Address Sexual Violence - Kamalludin, Iqbal; Pratami, Bunga Desyana; Khasna, Syarifa; Yaqin, Alamul; Umar, Achmad Jauhari (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2024)
Handling sexual violence cases requires a holistic, human rights-based approach, encompassing prevention, protection, law enforcement, recovery, and ensuring victims' access to justice. Islam advocates equality for all, but its implementation is constrained by the improper handling of many sexual violence cases due to the non-retroactive Sexual Violence Law. This paper proposes the urgency of upholding the principle of retroactivity in criminal law and Fiqh Jinayah to build an anti-sexual violence construction based on justice and equality. This normative juridical research employs conceptual, statutory, philosophical, and historical approaches. This approach provides an in-depth understanding of the concept of justice in the handling of sexual violence, according to Sharia. This study uses the Islamic legal literature and comparative legal studies to examine the urgency of upholding the retroactive principle in criminal law and Fiqh Jinayah. This study confirms that applying the retroactive principle to sexual violence is consistent with the six characteristics of Maqasid Sharia: cognitive nature, interconnectedness, wholeness, openness, multidimensionality, and purposefulness. The retroactive principle is necessary in cases of sexual violence as the primary rule in addressing such crimes, in addition to complementing existing laws and regulations. This principle is crucial to ensure fair law enforcement in cases of sexual violence.